Teacher motivation, quality instruction, and student outcomes: Not a simple path. (December 2021) - Woolfolk Hoy, Anita
Abstract: In this commentary, I briefly describe the assumptions of the researchers, then consider what we have learned from the studies in this issue about the links between teacher motivation, instruction, and student perceptions and how best to study these links. Next, I describe three surprises and two concerns about the work reported. In discussing the implications of the research in this issue, I raise several questions that could be investigated to help us understand why teacher and student perceptions might differ and what can be done to bring them into better alignment. Finally, I explore some implications of these studies for teacher education.